IMPLEMENTASI KURIKULUM MERDEKA MELALUI METODE BERMAIN KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN SOSIAL DAN EMOSIONAL ANAK USIA DINI DI UPT. TK NEGERI PEMBINA LIMA PLUH KECAMATAN LIMA PULUH KABUPATEN BATU BARA - Nurul Saputri; RIZKA RAMANDA; DITA WIDIYANTI; NOVITA YOLANDA; NURLIYAH NASUTION (Jurnal Al Athfaal, 2023)
Preparing a new curriculum is not easy for every education unit, it often becomes a polemic felt by educators, especially at the early childhood level. The curriculum is the main idea of ​​the educational process, without a good curriculum the learning process cannot run well so that national education goals cannot be achieved. To increase understanding regarding how an independent curriculum in Early Childhood Education is needed, a deeper discussion is needed regarding the study of the concept of its content and how the concept is actualized and implemented. This research aims to discuss the development and implementation of the independent curriculum in early childhood education, which includes the meaning of the independent curriculum, the characteristics and characteristics of the independent curriculum, and the stages of implementing the independent curriculum at the PAUD level. The method used is a descriptive qualitative method that uses theoretical analysis and literature study. The results of this research are. The independent study program is in accordance with the concept of independent learning put forward by the Ministry of Education and Culture. When preparing a standalone program, attention should be paid to the basic framework and structure of the program.